Knowledge Transfer in Community Schools: Factors Influencing Perspective - Rai, Rahan Singh (Journal of Management, 2022)
Purpose. This study examines the knowledge transfer through knowledge and communication-related factors in the context of Secondary Level (+2) education in Community Schools.Design & Approach. To obtain the objectives of this paper, data has been collected from the respondents of +2 level students of nine Community Schools and the schools have been selected using the key informant method. The respondents have asked structured questionnaire based on five-point Likert scales. While selecting the 430 respondents from different nine Community Schools, the researcher applies a purposive sampling method and the same count of questionnaires have been distributed to them, among these, with the final net count of 403 filled-up questionnaires taken for the study. To analyze the data, statistical tools such as frequency, percentage etc. have been used. Cronbach's alpha is observed to test the reliability of items. Similarly, Pearson's Correlation coefficient is used to examine the relationship between the Knowledge Transfer-dependent variable and the other four independent variables. Furthermore, multiple regression analysis is also performed for the testing of the hypothesis.Originality & Value. In the context of factors influencing knowledge transfer perspective in Community Schools, this paper made deep research through the various dimensions of knowledge transfer and which may assist the various stakeholders with regard to provide and improve the way out of quality education.Results & Findings. The major findings of the study were that Sharing of Understanding and Communication Competence has significant effect on knowledge transfer whereas, Information Technology, and Source Credibility has positive but insignificant impact on knowledge transfer.